Meningkatkan Motivasi Belajar Siswa Dalam Mata Pelajaran Seni Budaya Melalui Media Audiovisual di SMA Negeri 1 Bonjol - Elfina Firman; Ardipal Ardipal (SENDRATASIK UNP, 2021)
This research aims to increase students' learning motivation by using audiovisual media on cultural arts lessons.This type of research is classroom action research. This study was conducted in two cycles. The object of the study was a student of class XI MIPA 1 Sma Negeri 1 Bonjol which amounted to 36 students who were divided into 2 sessions, namely odd sessions and even sessions. Research instruments are student motivation observation sheets and questionnaires. The data collection techniques used are observation, interview, questionnaire, documentation. The results showed that there was an increase in students' learning motivation in cultural arts subjects in class XI MIPA 1 using audiovisual media. This can be seen from each indicator experiencing an increase. On happy indicators with an average of 60% increased to 78%, attention indicators with an average of 47% increased to 67%, concentration indicators with an average of 44% increased to 76%, persistence indicators with an average of 38% increased to 65%. The average observation results in cycle I, which is 47% categorized as moderate and experiencing an increase in cycle II, which is 71% categorized as high. In addition to the observations of student learning motivation there are also angket results that increase in cycle I by 77% and disiklus II by 86%. Thus the author concluded that by using audiovisual media on cultural arts learning can increase the motivation of learning students of class XI MIPA 1 Sma Negeri 1 Bonjol.